Waste Meretrix meretrix Shell as Adsorbent of Copper (Cu2+) - Encik Weliyadi; Afni Nidyasari; Tri Paus Hasiholan Hutapea (Journal of Tropical Life Science, 2022)
Meretrix meretrix was found to be a very abundant waste at Amal Beach, Tarakan City. M. meretrix waste can reduce heavy metals, especially heavy metals copper (Cu2+), by the adsorption process. Research has been carried out on M. meretrix as an adsorbent of heavy metals copper (Cu2+) using the adsorption method of Shacker through chemical activation using NaOH bases. The SEM results showed that M. meretrix before activation had a rough pore surface that was still closed but M. meretrix after activation had a open pore surface that is why it could be used as an adsorbent. M. meretrix contains Al (Aluminum), which can be used as an adsorbent. The adsorption results showed that M. meretrix with activation in the Freundlich isotherm had the highest ability to absorb Cu2+ as much as 9,108 mg/g compared to without activation only 0.051 mg/g. It can be concluded that M. meretrix waste can be used as an absorbent of Cu2+ heavy metals.